2018
DOI: 10.1161/strokeaha.117.018700
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke Profile, Risk Factors, and Outcomes in India

Abstract: These comprehensive and novel clinical imaging data will prove useful in refining stroke guidelines and advancing stroke care in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 8 publications
11
47
1
Order By: Relevance
“…India lacks emergency medical services; studies have shown that from 1.5% to less than 10% of patients reach hospitals by ambulance. 10,11 The onset-to-door and treatment time is longer that before COVID-19 12 and it is likely to increase further, as observed in many severely affected countries, thereby compromising acute care. 9 Stroke patients from remote areas of the country are at greater risk of not reaching hospitals because of the suspension of public transport.…”
Section: Acute Stroke Carementioning
confidence: 99%
See 2 more Smart Citations
“…India lacks emergency medical services; studies have shown that from 1.5% to less than 10% of patients reach hospitals by ambulance. 10,11 The onset-to-door and treatment time is longer that before COVID-19 12 and it is likely to increase further, as observed in many severely affected countries, thereby compromising acute care. 9 Stroke patients from remote areas of the country are at greater risk of not reaching hospitals because of the suspension of public transport.…”
Section: Acute Stroke Carementioning
confidence: 99%
“…India has a higher burden of rheumatic heart diseases compared with developed countries; afflicted patients require vitamin K antagonists for anticoagulation and secondary stroke prevention. 10,21 Hence, the proportion of anticoagulated patients using warfarin, acenocoumarol, or related drugs is likely to be comparable to those using nonvitamin K-antagonist or -anticoagulation. 10,21 Patients generally have poor knowledge of the optimal use of anticoagulation and monitoring, which is likely to worsen further with decreased interaction with physicians.…”
Section: Poststroke Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Global Burden of Diseases study revealed nearly 5.87 million people were affected in stroke related deaths occurred in 2010 [6,4]. It was compared with 1990 statement (4.66 million) was increased by 1.2 million people were affected by stroke [7,8]. The past two decades 26% increased in stroke related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The past two decades 26% increased in stroke related deaths. The mortality of stroke is occurred 20 -30% in the 1 st month and 60% of survivors are dependent [9,8].…”
Section: Introductionmentioning
confidence: 99%